SISTEM MONITORING KARYAWAN PT ATHAYASA MANDIRI MENGGUNAKAN GPS BERBASIS ANDROID - Ridwan, RIDWAN; Rahmat Fauzi (Computer Science and Industrial Engineering, 2025)
PT Athayasa Mandiri, specializing in heavy equipment and forklift maintenance, faces challenges in real-time monitoring of field technicians due to an ineffective manual system, resulting in delays and reduced service quality. To address this, an Android-based monitoring application is developed using GPS for location tracking and Google Maps API for navigation and route optimization. Built with Flutter for a modern interface and Firebase for reliable data storage, the application adopts the Design Thinking methodology to address user needs, including technicians and management. Key features include real-time location verification, travel history reports, and schedule monitoring, minimizing potential fraud while enhancing task coordination. This system improves transparency, accelerates decision-making, and boosts operational efficiency, reducing costs and increasing customer satisfaction. Additionally, the application is designed to support future IoT integration, providing strategic value and strengthening the company’s competitiveness in the industrial market.